Taṣawwuf- Islamic Mysticism (Prilozi za orijentalnu filologiju, 2017)
The problem of Taṣawwuf, both as a doctrine and as a practice, represents a very large and complex theme Which cannot be discussed in the terms and by the standards of a different world, like the European for instance. Neither can it be considered in an isolated way, as a specific spiritual activity; on the contrary, it must be viewed as part of that complex phenomenon called Islam and its civilization, as part of a process in which spiritual and religious, social and political elements are miraculously interwoven and interconnected and in which two basis factors, the exoteric and the esoteric, have been confronted, each of these having its base booth in the Koran and in the corpus of tradition.Taṣawwuf starts from the esoteric exegesis of the Koran and the corpus of tradition, especially from those place which point directly to such a possibility and which contain deep metaphysical and anthropological-epistemological problems concerning God, cosmos and man, thus developing a corresponding hermeneutics as well.In the course of long centuries of its development Islamic mysticism has had a considerable influence on the formation of the ideology of Islamic culture: this is true of its early phase which is characterized by a prominent note of asceticism (zuhd) and fear of God's unlimited powers - not ascetici.sm as a usual renunciation of everyday needs and sensual acts in life but a profound ethical thought which is transformed into a metaphysical system of total renunciation of all that is not the fundamental and only existing essence, God - through developing of zuhd into a 'Category of love towards God (ma'l],abbat) - as it i:s true of the period of its complete maturity. Not only this- by its world view, its anthropology and universal ethics, its rich metaphysics which has hardly an equal in other great religions, Taṣawwuf has greatly influenced the configuration of the entire spiritual culture which gave birth to a special art, particularly literature. On the other hand, as an antithesis to the legalistic and literalistic Islam, Shiism with its teachings has also completed this truly complex structure of medieval Islamic ideology.